Comparative effectiveness of bone-protective interventions for aromatase inhibitors-induced bone loss in postmenopausal women with early breast cancer: a network meta-analysis - Xu, Yonghui; Lai, Junjie; Mai, Minjun; Tang, Yi; Wu, Zhouhan (Frontiers in Oncology, 2026)
ObjectivesThis network meta-analysis (NMA) aims to compare the efficacy of bone-protective interventions in preventing AIs-induced bone loss at lumbar spine and hip sites.MethodsWe systematically searched PubMed, Embase, Cochrane Library, Web of Science, and clinical trial registries from inception to February 28, 2025, to identify randomized controlled trials (RCTs) evaluating bone-protective interventions in postmenopausal women with breast cancer receiving AI therapy. Primary outcomes were changes in bone mineral density (BMD) at lumbar spine and total hip at 12 and 24 months. Network meta-analysis was performed using Bayesian methods with R software and WinBUGS. Treatment rankings were assessed using surface under the cumulative ranking curve (SUCRA) values.ResultsSeventeen RCTs involving 6,932 postmenopausal patients were included, comparing six interventions: denosumab, alendronate, zoledronic acid, ibandronate, risedronate, and eldecalcitol plus risedronate. At 12 months, denosumab demonstrated superior lumbar spine BMD improvement (SUCRA = 0.88, WMD = 5.63, 95% CI: 4.67-6.59), while ibandronate showed optimal hip BMD preservation (SUCRA = 0.94, WMD = 4.23, 95% CI: 2.91-5.43). At 24 months, denosumab maintained its advantage for lumbar spine (SUCRA = 0.83, WMD = 7.96, 95% CI: 5.38–10.52), whereas eldecalcitol plus risedronate showed the highest SUCRA ranking for hip preservation (SUCRA = 0.83, WMD = 6.38, 95% CI: 3.38–9.61). All active interventions significantly outperformed calcium plus vitamin D supplementation alone. Given that the eldecalcitol plus risedronate regimen was evaluated in only one randomized trial with a relatively small sample size, this finding should be interpreted cautiously.ConclusionAmong single agents, denosumab provides superior lumbar spine bone protection while ibandronate offers optimal hip bone preservation in AI-treated breast cancer patients. For extended therapy, combination regimens incorporating eldecalcitol with risedronate may show promising hip bone protection, though this conclusion is based on a single small-sample study and requires further validation. These findings support site-specific and duration-dependent treatment selection strategies. Further head-to-head trials are warranted to validate optimal treatment sequences.Clinical trial numberPROSPERO (CRD420251008444).